Analysis of Resource Potential And Economic Problems of Extraction of Petroleum in Ukraine with Hydrocarbon Deposits, the Stock of Which Belongs to the Category of Hard Extractive - Витвицький, Я. С.; Пілка, М. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The analysis of possibilities of increasing the recovery of oil in Ukraine by using potential resources of fields with hard-recoverable stocks has been carried out. The criteria for identifying individual deposits as hard-recoverable oil, structure of hard-recoverable stocks, development features have been presented. Economic problems in developing hardrecoverable stocks of oil and ways to overcome them have been considered.